2020
DOI: 10.12737/stp-64202012
|View full text |Cite
|
Sign up to set email alerts
|

Earthquakes and Geomagnetic Disturbances

Abstract: The article addresses the problem of the connection of earthquakes with geomagnetic phenomena. We have carried out an experimental study using a method based, firstly, on the separation of periods of geomagnetic activity into extremely quiet and disturbed, and, secondly, on the description of seismic activity with an index called the global daily magnitude (GDM). By analyzing the NEIC earthquake catalog of the US Geological Survey over a 20-year period from 1980 to 1999, we have shown that the planetary activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The relationship between the earthquakes and geomagnetic phenomena was established recently [9] [10]; the authors separated periods of geomagnetic activity into very quiet and extremely disturbed, and then correlated them with seismic activity. By analyzing the NEIC earthquake catalog of the US Geological Survey over a 20-year period, from 1980 to 1999, it was shown that the planetary activity of earthquakes under quiet geomagnetic conditions is noticeably higher than the activity under disturbed conditions.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 99%
“…The relationship between the earthquakes and geomagnetic phenomena was established recently [9] [10]; the authors separated periods of geomagnetic activity into very quiet and extremely disturbed, and then correlated them with seismic activity. By analyzing the NEIC earthquake catalog of the US Geological Survey over a 20-year period, from 1980 to 1999, it was shown that the planetary activity of earthquakes under quiet geomagnetic conditions is noticeably higher than the activity under disturbed conditions.…”
Section: Magnetically Controlled Seismicitymentioning
confidence: 99%